2017
DOI: 10.11648/j.jgo.20170505.11
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean Section Without Using Bladder Catheterization Is Safe in Uncomplicated Patients

Abstract: A case -control study was carried out to assess whether carrying out caesarean section without urethral catheterization is safe in terms of intraoperative safety, prevalence of UTI, and the rate of the first voiding discomfort. It was conducted At Al Thawra General Hospital over a period of eight months (From Feb 1 st to Sep 30 th 2015). One hundred women who admitted to delivery unit and delivered by cesarean section were enrolled in the study. They were divided randomly into study group (non catheterized, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Removing the urethral catheter earlier may reduce the incidence of significant bacteriuria, encourage early ambulation, and may shorten the hospital stay post caesarean delivery. 3 , 4 , 6 , 7 , 10 The policy of 8-h urethral catheter removal post surgery may encourage post-operative patients to get off the hospital bed and micturate by themselves, thus achieving early mobilization which discourages the formation of deep venous thrombosis. 10 There is lack of evidence on the use of 8-h urethral catheter removal post caesarean section.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Removing the urethral catheter earlier may reduce the incidence of significant bacteriuria, encourage early ambulation, and may shorten the hospital stay post caesarean delivery. 3 , 4 , 6 , 7 , 10 The policy of 8-h urethral catheter removal post surgery may encourage post-operative patients to get off the hospital bed and micturate by themselves, thus achieving early mobilization which discourages the formation of deep venous thrombosis. 10 There is lack of evidence on the use of 8-h urethral catheter removal post caesarean section.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 The advocacy for elective caesarean delivery under spinal anaesthesia rather than general anaesthesia revolves around reduced morbidity and mortality risks associated with spinal anaesthesia. [5][6][7] Spinal anaesthesia may, however, affect the lower urinary tract innervation 8,9 and leading to a delay in the time of first voiding and ultimately urinary retention with prevalence ranging from 0.05% to 14.1%, following vaginal delivery, and between 3.3% and 24.1% after caesarean delivery. 4 Zanfini et al 8 showed that up to 80% of urinary bladder function is regained 8 h following spinal anaesthesia.…”
Section: Introductionmentioning
confidence: 99%